Fabrication and field emission properties of poly-diamond films - Ju, BK; Lee, YH; Oh, MH (ELSEVIER ADVANCED TECHNOLOGY, 1998)
By using a substrate transferring technique, poly-diamond thick films having a smooth or rough surface could be fabricated as field emitter materials. The diamond film with a smooth surface, which was transferred from the interface between the (100) Si substrate and poly diamond deposited by plasma-enhanced CVD, showed better field emission properties in terms of emission current density with improved vacuum level dependence as compared with original poly-diamond film from a rough surface. (C) 1998 Elsevier Science Ltd. All rights reserved.